The influence of scuba divers’ personality, experience,and demographic profile on their underwater behavior - Musa, G.; Seng, W.T.; Thirumoorthy, T.; Abessi, M. (Cognizant Communication Corporation, 2011)

(untitled)
Scuba diving activity is known to cause detrimental impact on the marine environment and its sustainability. This study explores the influence of divers’ personality, experience, and demographic profile on their underwater behavior. Data were collected using convenience sampling among divers in Malaysia. A total of 302 questionnaires were returned and analyzed. The results show that divers are generally responsible underwater. Scuba diving experience parameters of duration of involvement, number of dives, self-rating experience, and diving frequency influence underwater behavior. Divers with high neuroticism are more likely to be irresponsible, while high agreeableness personality factor is related to more responsible behavior underwater. Based on the results the authors provide some managerial recommendations in order to promote responsible scuba diving activities.